THE INTANGIBLE CULTURAL HERITAGE OF MINANGKABAU TRADITIONAL EXPRESSIONS: The Local Wisdom of the Society in Advising and Noble Advicing - Hasanuddin W.S. (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2016)
WARISAN BUDAYA TAKBENDA UNGKAPAN TRADISIONAL MINANGKABAU: Kearifan Lokal Masyarakat tentang Tunjuk Ajar dan Nasihat-nasihat MuliaAbstractThis paper contains a discussion of oral tradition traditional expression of Minangkabau proverb within the framework of the research of oral literature and folklore. Traditional expressions are related to advise about wisdom and belief, while belief is closely linked to the traditions and customs. All of which are summarized in two main points, namely culture and ideology. The ways to convey the noble advice through traditional expression uttered by using parables and comparisons which the meaning conveyed figuratively (indirectly), is one of the local wisdoms in Minangkabau community in building character education. Parables and comparisons can be made by refering to the properties and characteristics of plants (flora), animal (fauna), or on human behavior. It is important to categorize the parables and comparisons contained in traditional expressions of the Minangkabau proverbs. The categorization is formulated based on the real categorization made by the owner of intagible cultural heritage, namely the Minangkabau society. Based on this categorization, it can be identified the local wisdom about how the Minangkabau people give advice to the society in developing the society integrity, social control, blending the shattered power for social solidarity, group identity, and maintaining communal harmony.Keyword: intagible cultural heritage, category, traditional expression proverb, Minangkabau society AbstrakMakalah ini berisi pembahasan tentang tradisi lisan ungkapan tradisional peribahasa Minangkabau dalam kerangka penelitian sastra lisan dan folklor. Ungkapan tradisional peribahasa berkaitan dengan tunjuk ajar kearifan dan keyakinan, sedangkan keyakinan berhubungan erat dengan tradisi dan kebiasaan. Kesemuanya itu terangkum pada dua hal pokok, yaitu kebudayaan dan ideologi. Cara menyampaikan tunjuk ajar nasihat-nasihat mulia melalui ungkapan tradisional yang diutarakan dengan menggunakan bahasa perumpamaan dan perbandingan yang maknanya disampaikan secara kias (tidak langsung), merupakan salah satu kearifan lokal masyarakat Minangkabau di dalam menanamkan pendidikan karakter. Perumpamaan dan perbandingan dapat dilakukan dengan merujuk pada sifat dan karakteristik tumbuh-tumbuhan (flora), hewan (fauna), atau pada perilaku manusia. Perumpamaan dan perbandingan yang terdapat di dalam ungkapan tradisional peribahasa Minangkabau penting dirumuskan pengkategoriannya. Pengkategorian dirumuskan berdasarkan pengkategorian yang sesungguhnya telah dilakukan oleh masyarakat pemilik warisan budaya tak benda ini, yaitu masyarakat Minangkabau. Berdasarkan pengkategorian ini sekaligus dapat diidentifikasi kearifan lokal tentang bagaimana masyarakat Minangkabau melakukan tunjuk ajar di dalam mengembangkan integritas masyarakat, melakukan kontrol sosial, memadukan kekuatan bersama yang terpecah untuk solidaritas sosial, identitas kelompok, dan menjaga harmonisasi komunalnya.Kata kunci: warisan budaya tak benda, kategori, ungkapan tradisional peribahasa, masyarakat Minangkabau